Resource Availability Drives Responses of Soil Microbial Communities to Short-term Precipitation and Nitrogen Addition in a Desert Shrubland - She, Weiwei; Bai, Yuxuan; Zhang, Yuqing; Qin, Shugao; Feng, Wei; Sun, Yanfei; Zheng, Jing; Wu, Bin (Frontiers in Microbiology, 2018)
Desert microbes are expected to be substantially sensitive to global environmental changes, such as precipitation changes and elevated nitrogen deposition. However, the effects of precipitation changes and nitrogen enrichment on their diversity and community composition remain poorly understood. We conducted a field experiment over two years with multi-level precipitation and nitrogen addition in a desert shrubland of northern China, to examine the responses of soil bacteria and fungi in terms of diversity and community composition, and to explore the roles of plant and soil factors in structuring microbial communities. Water addition significantly increased soil bacterial diversity and altered the community composition by increasing the relative abundances of stress-tolerant (dormant) taxa (e.g., Acidobacteria and Planctomycetes); however, nitrogen addition had no substantial effects. Increased precipitation and nitrogen did not impact soil fungal diversity, but significantly shifted the fungal community composition. Specifically, water addition reduced the relative abundances of drought-tolerant taxa (e.g., the orders Pezizales, Verrucariales, and Agaricales), whereas nitrogen enrichment decreased those of oligotrophic taxa (e.g., the orders Agaricales and Sordariales). Shifts in microbial community composition under water and nitrogen addition occurred primarily through changing resource availability rather than plant community. Our results suggest that water and nitrogen addition affected desert microbes in different ways, with watering shifting stress-tolerant traits and fertilization altering copiotrophic/oligotrophic traits of the microbial communities. These findings highlight the importance of resource availability in driving the desert microbial responses to short-term environmental changes.